2020
DOI: 10.1136/rapm-2019-101141
|View full text |Cite
|
Sign up to set email alerts
|

Does cryoneurolysis result in persistent motor deficits? A controlled study using a rat peroneal nerve injury model

Abstract: BackgroundCryoneurolysis of peripheral nerves uses localised intense cold to induce a prolonged block over multiple weeks that has the promise of providing potent analgesia outlasting the duration of postoperative pain following surgery, as well as treat other acute and chronic pain states. However, it remains unclear whether persistent functional motor deficits remain following cryoneurolysis of mixed sensorimotor peripheral nerves, greatly limiting clinical application of this modality. To help inform future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…100 Importantly, treatment with 10% procaine HCl to intercostal nerves within the same animal study resulted in similar deficit and recovery patterns. 100 In contrast, three preclinical studies designed specifically to address this issue revealed no long-term changes to the structure or function of mixed nerves and their motor targets after tibial or common peroneal nerve cryoneurolysis and subsequent axonal regeneration and remyelination 99,101,102 -even with repeated applications. 101…”
Section: Percutaneous Application To Acute Painmentioning
confidence: 99%
See 1 more Smart Citation
“…100 Importantly, treatment with 10% procaine HCl to intercostal nerves within the same animal study resulted in similar deficit and recovery patterns. 100 In contrast, three preclinical studies designed specifically to address this issue revealed no long-term changes to the structure or function of mixed nerves and their motor targets after tibial or common peroneal nerve cryoneurolysis and subsequent axonal regeneration and remyelination 99,101,102 -even with repeated applications. 101…”
Section: Percutaneous Application To Acute Painmentioning
confidence: 99%
“…11 However, various investigators have suggested the possibility of subclinical residual and persistent motor weakness caused by either incomplete regeneration or motor unit clustering. 99 There are preclinical data from laboratory animals suggesting decreased nerve conduction velocities 90 days after cryoneurolysis of intercostal nerves, but all physiologic and behavioral measures fully returned to normal by that time point (subsequent time points were not evaluated). 100 Importantly, treatment with 10% procaine HCl to intercostal nerves within the same animal study resulted in similar deficit and recovery patterns.…”
Section: Percutaneous Application To Acute Painmentioning
confidence: 99%
“…The complications described are minimal (local hematomas), there is no evidence of permanent nerve damage or neuroma, and only one serious case of myonecrosis and abscess has been described. 15,[23][24][25][26][27][28] In our series, there were no serious complications related to the technique. Nausea and vomiting were present in 95.8% of patients and most related it to opioid use.…”
Section: Discussionmentioning
confidence: 46%
“…[ 32 ] No other reports of permanent nerve damage, neuroma formation, or deafferentation pain have been published. [ 33 34 35 ]…”
Section: Discussionmentioning
confidence: 99%